1989
DOI: 10.1295/polymj.21.725
|View full text |Cite
|
Sign up to set email alerts
|

Living Cationic Polymerization of Vinyl Monomers by Organoaluminum Halides V. Polymerization of Isobutyl Vinyl Ether with EtAlCl2 in the Presence of 2,6-Dimethylpyridine and Related Amines

Abstract: ABSTRACT:In the presence of 2,6-dimethylpyridine as an added base, living cationic polymerization of isobutyl vinyl ether was achieved in n-hexane at O to +40°C with the 1-(isobutoxy)ethyl acetate (3)/ethylaluminum dichloride [CH3CH(OiBu)-OCOCH3/EtAICl2] initiating system. A low concentration of the pyridine, 4 times that of the cationogen 3 ( or the active end), was sufficient for the living process. Without the added amine, the polymerization was almost instantaneous and nonliving. The use of triethylamine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Complex formation with a Lewis acid catalyst40–42 and interaction with a carbocation43 are also reported as additional roles of DTBP in some studies, although others claim there is no proof of this 44, 45. In polymerization of IBVE with IBVE–AcOH/EtAlCl 2 initiating systems,46 a large amount (1.0 M) of DTBP has little effect on the rate and control of the reaction, which indicates that DTBP cannot interact with the propagating species derived from IBVE. In addition, adventitious water does not initiate the polymerization using metal oxides, although it may induce undesired reactions such as chain transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Complex formation with a Lewis acid catalyst40–42 and interaction with a carbocation43 are also reported as additional roles of DTBP in some studies, although others claim there is no proof of this 44, 45. In polymerization of IBVE with IBVE–AcOH/EtAlCl 2 initiating systems,46 a large amount (1.0 M) of DTBP has little effect on the rate and control of the reaction, which indicates that DTBP cannot interact with the propagating species derived from IBVE. In addition, adventitious water does not initiate the polymerization using metal oxides, although it may induce undesired reactions such as chain transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Cationic polymerization of IBVE was investigated in the presence of DMA. It was previously reported that strong bases such as amides or amines were the possible terminating agents or inhibitors for the cationic polymerization through electrostatic interactions with growing carbocations or Lewis acids 2(b), 4(a), 15, 17. To investigate the effect of DMA on the polymerization behavior, cationic polymerization of IBVE was examined using EtAlCl 2 or SnCl 4 in the presence of DMA in toluene at 0 °C ([IBVE] 0 = 0.76 M, [IBVE‐HCl] 0 = 4.0 mM, [Lewis acid] 0 = 5.0 mM).…”
Section: Resultsmentioning
confidence: 99%
“…In this article, cationic polymerization of an alkyl vinyl ether using various Lewis acids, including Et x AlCl 3− x and SnCl 4 , in the presence of an amide or an amine was examined. Such strong bases have rarely been used for the polymerization of vinyl ethers 10, 15. Therefore, polymerization with a strong base was compared to the conventional counterpart with a weak base, specifically focusing on the scope of adaptable Lewis acids and the relationship between basicity and the optimum amount of added bases.…”
Section: Introductionmentioning
confidence: 99%
“…Since most cationic polymerizations involve an equilibrium between covalent adducts and ionic species, the equilibrium can be shifted from free ions to dormant covalent species by adding a salt with a common counteranion. 104 Alternatively, the carbenium ions can be deactivated with nucleophiles, such as phosphines, 105 hindered arnines, 106 dialkyl sulfides, 107…”
Section: Cationic Polymerizations Of Olefinsmentioning
confidence: 99%